Flexible Spiking CPGs for Online Manipulation During Hexapod Walking - Strohmer, Beck; Manoonpong, Poramate; Larsen, Leon Bonde (Frontiers in Neurorobotics, 2020)
Neural signals for locomotion are influenced both by the neural network architecture and sensory inputs coordinating and adapting the gait to the environment. Adaptation relies on the ability to change amplitude, frequency, and phase of the signals within the sensorimotor loop in response to external stimuli. However, in order to experiment with closed-loop control, we first need a better understanding of the dynamics of the system and how adaptation works. Based on insights from biology, we developed a spiking neural network capable of continuously changing amplitude, frequency, and phase online. The resulting network is deployed on a hexapod robot in order to observe the walking behavior. The morphology and parameters of the network results in a tripod gait, demonstrating that a design without afferent feedback is sufficient to maintain a stable gait. This is comparable to results from biology showing that deafferented samples exhibit a tripod-like gait \citep{mantziaris2017intra} and adds to the evidence for a meaningful role of network topology in locomotion. Further, this work enables research into the role of sensory feedback and high-level control signals in the adaptation of gait types. A better understanding of the neural control of locomotion relates back to biology where it can provide evidence for theories that are currently not testable on live insects. In engineering, the use of spiking neural networks for robot locomotion facilitates the use of low-power, neuromorphic hardware, enabling new applications on significantly smaller robots or direct interfacing with biological tissue.